Spa as Arena of Career Woman Resistance to Patriarch Domination - Bhernadetta Pravita Wahyuningtyas (Humaniora, 2011)
This study examines the career women who use the habit of treating the body through the routine of coming to spas, which aims to overcome the dominance of patriarchy. This study uses several concepts. First, muted group theory, which states that woman, is the one that silenced; so to overcome this condition, women should perform self-transformation. The transformation is aligned with the second concept, feminist existentialist, which defines the transformation as the change of a woman concept from Other to Self. The transformation can be achieved not only by working outside the domestic sphere, but also supported by a good appearance through a complete body treatment. Grooming habits acquired through socialization that derived in woman since their childhood. The socialization is about how women as a person who is considered weak by the world of patriarchal domination using the power of their beauty to master, subdue, and break the domination in her life. Then, with their good appearance, woman can express their existence in everything that they do from object become subject. Spa and the whole result of the activities contained in it then consciously become a way of resistance that being used by the career woman against the domination of patriarchy which overshadowing their lives.